Sanctuaries, “Special Needs,” and Service: Religious Leader Perceptions on Including Children with Disability - Stewart-Ginsburg, Jared H. (Journal of disability & religion, 2020)
Religion can play an important role in the life of a family of a child with a disability, but children with disabilities and their family members often reported they did not feel supported in religious environments. Families often indicated religious leaders were a factor that can change perception. This study investigated the experience, knowledge, and attitudes of faith community leaders on including children with disabilities and their families in religious organizations. Participants included clergy and staff members who serve in leadership capacities. The study utilized a mixed-methods approach including an online survey and focus group meetings. This article reports the quantitative results. Participants reported inclusive attitudes, but varying experience and minimal training in this area. Trends found in responses were explored and corroborated to examine relationships between data sets and the body of literature.